Management - obecné pojetí a veřejný sektor - Siegl, Milan (Univerzita Pardubice, 2002)
At the beginning the management expansion dutiny the 20th century is described. Then the 21th century is shown in agreement with ideas of recognized futurologists and management leaders. Then the public sector's defined more precisely and furthermore the five basic managerial functions are summarized and completed with their major principles. In the second part of the paper innovations in public sector institutions are analyzed and the parts of innovation implementation and innovation acceleration are emphasized.
Keywords: Management; 20. století; 21. století; Inovace; veřejný sektor; manažerské činnosti